Suppression of CPSF6 Enhances Apoptosis Through Alternative Polyadenylation-Mediated Shortening of the VHL 3′UTR in Gastric Cancer Cells - Shi, Xinglong; Ding, Keshuo; Zhao, Qiang; Li, Pengxiao; Kang, Yani; Tan, Sheng; Sun, Jielin (Frontiers in Genetics, 2021)
Alternative polyadenylation (APA) is an important RNA post-transcriptional process, which can generate diverse mRNA isoforms. Increasing evidence shows that APA is involved in cell self-renewal, development, immunity and cancer. CPSF6 is one of the core proteins of CFIm complex and can modulate the APA process. Although it has been reported to play oncogenic roles in cancer, the underlying mechanisms remain unclear. The aim of the present study was to characterize CPSF6 in human gastric cancer (GC). We observed that CPSF6 was upregulated in GC. Knockdown of CPSF6 inhibited proliferation and enhanced apoptosis of GC cells both in vitro and in vivo. Global APA site profiling analysis revealed that knockdown of CPSF6 induced widespread 3′UTR shortening of genes in GC cells, including VHL. We also found CPSF6 negatively regulated the expression of VHL through APA and VHL short-3′UTR isoform enhanced apoptosis and inhibited cell growth in GC cells. Our data suggested that CPSF6-induced cell proliferation and inhibition of apoptosis were mediated by the preferential usage of poly(A) in VHL. Our data provides insights into the function of CPSF6 and may imply potential therapeutic targets against GC.